S-1-based concurrent chemoradiotherapy plus nimotuzumab in patients with locally advanced esophageal squamous cell carcinoma who failed neoadjuvant therapy: a real-world prospective study - Xin Wang; Guojie Feng; Xiongtao Yang; Nuo Yu; Ziyu Zheng; Jiao Li; Xiaozheng Kang; Xiankai Chen; Ruixiang Zhang; Yong Li; Zhen Wang; Lei Deng; et al. (Cancer Biology & Therapy)
Purpose This prospective study in a real-world setting investigated the feasibility and safety of S-1 plus nimotuzumab (S-1-Nimo) based concurrent chemoradiotherapy (CCRT) in locally advanced esophageal squamous cell carcinoma (LA-ESCC) patients who failed to neoadjuvant chemotherapy or chemoimmunotherapy.Methods LA-ESCC patients who failed to converse to resectable disease after neoadjuvant chemotherapy or chemoimmunotherapy were enrolled to receive the 4-week S-1-Nimo regimen of radiotherapy (40 Gy in 20 fractions, 5 days per week), S-1 chemotherapy, and nimotuzumab. Then, after surgical assessments, patients evaluated as resectable disease received surgery; patients with unresectable disease continued to receive definitive radiotherapy (50–60 Gy in 25–30 fractions, 5 days per week) concurrently with S-1-Nimo. The primary endpoint was event-free survival (EFS).Results Sixty-four patients were enrolled and evaluated. The median follow-up time was 23.2 months. Median EFS was 9.6 (95% confidence interval [CI], 7.1–14.0) months, with an estimated 2-year EFS rate of 24.2%. The median overall survival (OS) and the estimated OS rate at 2 years were 13.4 (95% CI, 10.3–17.5) months and 31.2%, respectively. Twelve underwent surgery, with a surgical conversion rate of 18.8% and an R0 resection rate of 100.0%. Subgroup analysis identified the significantly prolonged EFS and OS in patients who experienced radical surgery (median EFS, not reached vs. 8.7 months; p = .0117. median OS, 24.9 vs. 10.6 months; p = .0205) as compared to those treated with CCRT. Of 64 patients, grade 3 adverse events mainly included radiation esophagitis (4.7%), anemia (1.6%), and thrombocytopenia (1.6%).Conclusion The study demonstrated the reasonable efficacy and promising safety of the S-1-Nimo-based CCRT in LA-ESCC patients with failure to neoadjuvant chemotherapy or chemoimmunotherapy.